RENCANA PEMASARAN KEDAI MAKAN NDORO KAKUNG PLAZA AMBARUKMO YOGYAKARTA - , Henry Utama, Dr. Ike Janita Dewi, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is intended to get the results of a study about business development opportunities in the Ndoro Kakung and to develop a marketing plan that can be used as guidelines by management Ndoro Kakung. Research method used is a qualitative descriptive analysis method using primary and secondary data. The author identifies the environment both external environment and internal environment affecting the company. The next step is to formulate the key factors of success and pass analysis of the market, consumers and competitors. The final part of this study provide general advice on business development and marketing plans in particular. Thus providing an appropriate design strategy with the company's internal conditions and market opportunities. This study concluded that the company has improved alternatives starting from the application of STP, a change in concept and implementation of marketing plans.